PTSD symptoms among tsunami exposed mothers in Sri Lanka: the role of disaster exposure, culturally specific coping strategies, and recovery efforts. Issue 4 (4th July 2017) - Wickrama, Thulitha; Wickrama, K.A.S.; Banford, Alyssa; Lambert, Jessica
ABSTRACT: Background and objectives: Women in Sri Lanka have been uniquely exposed to a complex and protracted set of stressors stemming from a civil war conflict spanning over 25 years and the tsunami which struck Southeast Asia in 2004. This study investigates coping strategies and their association with trauma-related symptoms of tsunami-exposed mothers in Sri Lanka at two time points. Design: Data for this study come from surveys administered in two waves of data collection to investigate both mothers' and adolescent children's post-tsunami mental health in early 2005, three months after the tsunami struck, and again in 2008, three years later. Methods: Latent-variable structural equation modeling was used to test the study hypotheses among 160 tsunami-affected mothers in the Polhena village, Matara district, Sri Lanka. Results: Among the various coping strategies examined, the use of cultural rituals as well as inner psychological strength was associated with lower levels of posttraumatic stress symptoms. In contrast, passive religious beliefs were associated with greater posttraumatic stress levels. Conclusions: The results of this study reveal the differential associations of various coping strategies including rituals used by mothers exposed to the tsunami in Sri Lanka and their posttraumatic stress symptom levels.